Phosphorylation of the C-terminal tail of proteasome subunit ?7 is required for binding of the proteasome quality control factor Ecm29 - Wani, Prashant S.; Suppahia, Anjana; Capalla, Xavier; Ondracek, Alex; Roelofs, Jeroen (My University, 2017)
The proteasome degrades many short-lived proteins that are labeled with an ubiquitin chain. The identification of phosphorylation sites on the proteasome subunits suggests that degradation of these substrates can also be regulated at the proteasome. In yeast and humans, the unstructured C-terminal region of ?7 contains an acidic patch with serine residues that are phosphorylated. Although these were identified more than a decade ago, the molecular implications of ?7 phosphorylation have remained unknown. Here, we showed that yeast Ecm29, a protein involved in proteasome quality control, requires the phosphorylated tail of ?7 for its association with proteasomes. This is the first example of proteasome phosphorylation dependent binding of a proteasome regulatory factor. Ecm29 is known to inhibit proteasomes and is often found enriched on mutant proteasomes. We showed that the ability of Ecm29 to bind to mutant proteasomes requires the ?7 tail binding site, besides a previously characterized Rpt5 binding site. The need for these two binding sites, which are on different proteasome subcomplexes, explains the specificity of Ecm29 for proteasome holoenzymes. We propose that alterations in the relative position of these two sites in different conformations of the proteasome provides Ecm29 the ability to preferentially bind specific proteasome conformations.
Citation: Wani, P. S., Suppahia, A., Capalla, X., Ondracek, A., & Roelofs, J. (2016). Phosphorylation of the C-terminal tail of proteasome subunit ?7 is required for binding of the proteasome quality control factor Ecm29. Scientific Reports, 6. doi:10.1038/srep27873